Традиції копного судочинства в Україні - Сердюк, Наталія Аркадіївна; Serdiuk, Nataliia Arkadiivna (Київський національний університет імені Тараса Шевченка, 2015)
Статтю присвячено історико-правовому аналізу копного судочинства як особливої форми громадського судочинства в Україні та ролі виборного начала в його становленні. Проаналізовано правовий статус копних суддів та порядок їх обрання. Автор акцентує увагу, що народ сам стежив за громадським спокоєм і за дотриманням свого права та самостійно здійснював народну судову владу.

Appeals of historians of law to the study of the past have been justified and useful as awareness of the achievements and failures allows to protect the progress and not repeat the mistakes of the past. Community court as a social phenomenon requires deep historical research, philo sophical reflection and consistent legal interpretation. The historical experience of the exis tence of the Community proceedings indicates that there was a real justice mechanism, which effectively solved the conflict. Community court – is one of the main types of community court. Community, as the most com plete form of expression of the popular will, power and prestige as the authority was a gath ering of local residents for investigation and trial. The people had guaranteed the public calm and compliance with their rights and functions and had performed the judiciary of the people. Competence of Community Court extended to all residents of a territory, which were equal at the meeting. Community did not allow any restriction and considered almost all cases, without separation on criminal and civil cases. When it was at full strength (sometimes 100 people or more), from this part of the Community court by the community or by the plaintiff and defendant respect able persons were elected to act as judges. As the crime was understood in terms of damage to the owner, but not to the state or society, the injured (victim) or his family searched and chased criminals, convened the assembly and even a direct effect on the trial on the case. Thus, the role of the injured (victim) in the process was active even in criminal cases. The idea of Community court required the presence in it of all citizens of the area. Custom regarding the presence of all neighbors required not only assistance to be offended, all the neighbors were informed about what was going on it; also it clarified wheather anyone could provide information about the perpetrators of the crime who had not been disclosed. To take into consideration that the election of the judges in the community for a possibility to carry out their task and maintain an order in it, these judges could be equated to modern Collegium of Judges.
Traditions of community proceedings in Ukraine
Keywords: копний суд; громадський суд; копні судді; копний процес; компетенція копного суду; копа; копні звичаї; копне право; примирення; community court; community judges; community proceeding; competences of community court; community traditions; community right and reconciliation